Dynamical Analysis and Chaos Control in a Discrete-Time Evolutionary Beverton-Holt Model - Ch-Chaoui, Mohamed; Mokni, Karima (Discontinuity, Nonlinearity, and Complexity, 2026)
In this work, a discrete-time evolutionary Beverton-Holt population model is formulated. The existence and local asymptotic stability of the positive equilibrium point are studied. It is also shown that the discrete model can undergo a Neimark-Sacker bifurcation (NSB) in a small neighborhood of the positive equilibrium under certain conditions. In order to control chaos, we employ the Ott-Grebogi-Yorke (OGY) method and the hybrid control strategy to stabilize the unstable periodic orbits by using small perturbations applied to the derived system. Numerical simulations are developed with Matlab software, not only to verify our theoretical results but also to show more complex dynamics of the derived model, including invariant curves and chaotic sets.